Islamophobia and racism in America - Love, Erik Robert (New York University Press, 2017)
Islamophobia has long been a part of the problem of racism in the United States, and it has only gotten worse in the wake of shocking terror attacks, the ongoing refugee crisis, and calls from public figures like Donald Trump for drastic action. As America becomes a "majority-minority" nation, this strategic shift in American civil rights advocacy signifies challenges in the decades ahead, making Love's findings essential for anyone interested in the future of universal civil rights in the United States.